Using Process Writing Approach (PWA) to Teach Writing Descriptive Text - Fitri Novia; Eva Saptarina (Islamic State Institute of Bengkulu (IAIN) Bengkulu, 2021)
The research aim was to find out whether or not there was a significant difference in students' writing performance from descriptive passage among learners who practiced using the Process Writing Approach and those who were not. The design of that research used quasi-experimental. Participants were selected from X TKJ 3 being the experimental group and X TKJ 2 being the control group. Instruments of this study used a written test. There were five topics about the descriptive text in which students chose one of the issues. A paired sample t-test and independent-sample t-test were used to investigate the data. The outcome acquired from the paired sample t-test confirmed that students' writing achievement increased in the descriptive text after using the process writing approach. Independent-samples t-test analysis revealed that pvalue (0.008) was lower than άvalu (0.05). Further analysis indicated a significant difference in students' writing performance from a descriptive passage within learners who practiced using the Process Writing Approach.